The Effect of Spot Welding Parameters for Dissimilar Material Mild Steel and Galvanizes Steel on Nugget Size and Mechanical Strength - Azwar Azwar Hayat; La Ode Al Muslim; Ahmad Yusran Aminy (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2022)
The objective of this research was to analyze the effect of spot welding parameters on the size of the weld nugget and the maximum shear strength on dissimilar material mild steel and galvanized steel. The Taguchi and ANOVA methods were used to determine the welding parameters’ contribution to joint quality. Experimental design using Minitab-19 software with Taguchi method of 3 level 3 factor with L27 runs. Specimen size and dimensions were made using ASTM D1002 standard, with a plate thickness of 0.8 mm. Taguchi analysis S/N ratio data mean for weld nugget diameter with three levels of current used, 4 kA, 6 kA, and 8kA, shows the most influential on the diameter of the weld nugget was at 8 kA. The three levels of welding time used, 2s, 4s, and 6s, show the most influential on the diameter of the nugget the weld was at the third level for 6 seconds. It found that there was no significant difference in the size nugget at the three electrode pressure levels of 30 Ppsi, 40 Psi, and 50 Psi. Based on the tensile test and Taguchi analysis, the lowest shear strength was found in a weld nugget size of 3.15 mm at a welding current of 4 kA, a welding time of 2 seconds, an electrode pressure of 30 Psi, with a shear tensile strength of 300.19 N. Along with an increase in the size weld nugget correlated to an increase of shear strength. The highest shear tensile strength was found in the nugget size of 4.16 mm, with a welding current of 8 kA, welding time of 2 seconds, electrode pressure of 50 Psi, with a shear tensile strength of 3383.43 N. From the ANOVA, it found that the three factors of spot welding parameters were used, the most influential parameter in the formation of weld nuggets was welding current with a contribution of 84.86% then followed by welding time with a contribution of 14.86% and electrodes force with a contribution of 0.13%. Then from the three factors of spot welding parameters that were used the most influential parameter on the maximum shear tensile strength was the welding current with a contribution of 95.86 % then followed by welding time with a contribution of 0.52% and electrodes force with a contribution of 0.05%.